2018
DOI: 10.5505/kpd.2018.86548
|View full text |Cite
|
Sign up to set email alerts
|

Temperament and character dimensions, marital adjustment, and sexual satisfaction in couples with sexual dysfunction (eng)

Abstract: Object: The objective of the study is to investigate the differences in temperament and character dimensions, marital adjustment and sexual satisfaction between the couples with and without sexual dysfunction (SD). Methods: The study group consists of 78 married women and 23 married men with SD diagnosis according to DSM-IV-TR diagnostic criteria and also their spouses (n=202). The comparison group is composed of married couples without SD (n=200). The participants were applied Personal Information Form, Tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
(69 reference statements)
0
2
0
Order By: Relevance
“…The climacteric period in middle-aged women is the menopausal transition period associated with significant physiological and psychological changes [ 1 ]. In this period, reproductive changes such as decreased fecundity and approaching menopause, and physical changes in the sexual organs following the decline of sex hormones, affect the middle-aged women’s body image [ 2 ] and reduce their sexual satisfaction [ 3 , 4 ]. The feeling of femininity decline and the need to repair the relationship with the husband was one of the experiences that middle-aged women expressed following changes in their fertility [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The climacteric period in middle-aged women is the menopausal transition period associated with significant physiological and psychological changes [ 1 ]. In this period, reproductive changes such as decreased fecundity and approaching menopause, and physical changes in the sexual organs following the decline of sex hormones, affect the middle-aged women’s body image [ 2 ] and reduce their sexual satisfaction [ 3 , 4 ]. The feeling of femininity decline and the need to repair the relationship with the husband was one of the experiences that middle-aged women expressed following changes in their fertility [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these factors, middle-aged women are exposed to physical changes in the sexual organs due to the drop in sex hormones, which affects women's body image[ 10 ] and can be associated with a decrease in sexual satisfaction of middle-aged women. [ 11 12 13 ] Another study also showed that depressed middle-aged women have less sexual satisfaction than women who do not have depression. [ 14 ]…”
Section: Introductionmentioning
confidence: 99%